THE USE OF ANALYTICAL HIERARCHY PROCESS IN SELECTION BETWEEN BRIDGE CONSTRUCTION OR TUNNEL DUPLICATION ON THE MANADO OUTER RING ROAD 1 - Theo Kurniawan Sendow; Steve Christian Nixon Palenewen; Leidy Magrid Rompas (Jurnal HPJI (Himpunan Pengembangan Jalan Indonesia), 2026)
Abstract Sustained economic growth in Manado has led to increased traffic volume, particularly along the Manado Outer Ring Road I (MORR I) arterial route. A severe bottleneck occurs at the Tingkulu grade-separated junction, where the roadway narrows from 4 lanes (two-way) to 2 lanes (two-way) within the tunnel section. To address this issue, several alternatives were developed, including the construction of a 40-meter PCI girder bridge spanning MORR I above Tololiu Supit Road and the duplication of the 78-meter Aramco underpass tunnel. This study employs the Analytical Hierarchy Process method, with 5 operational criteria: economics, transpor-tation systems, traffic performance, environmental impact, and social aspects. Additionally, 10 multisectoral stakeholder groups served as expert evaluators. The study concludes that Alternative 1 (the construction of the PCI girder bridge) is the optimal choice. Keywords: Analytical Hierarchy Process; multi-sectoral analysis; operational criteria; traffic performance Abstrak Pertumbuhan ekonomi yang berkelanjutan di Kota Manado telah meningkatkan volume lalu lintas, khususnya di sepanjang jalan arteri utama Manado Outer Ring Road I (MORR I). Hambatan, berupa bottleneck, yang parah terjadi pada simpang tidak sebidang Tingkulu, yang mana pada segmen ini terjadi penyempitan badan jalan dari 4 lajur 2 arah menjadi 2 lajur 2 arah. Kondisi ini terjadi pada bagian terowongan. Untuk menghi-langkan persoalan yang ada, dibuat alternatif-alternatif pilihan, termasuk pembangunan jembatan PCI Girder sepanjang 40 m, yang melintasi Manado Outer Ring Road I di atas jalan Tololiu Supit, dan menduplikasi tero-wongan underpass Aramco sepanjang 78 m. Analisis pada studi ini menggunakan metode Analytical Hierarchy Process, dengan 5 kriteria operasional, yaitu ekonomi, sistem transportasi, kinerja lalu lintas, dampak lingkungan, dan aspek sosial. Selain itu, terdapat 10 kelompok pemangku kepentingan multi-sektoral bertindak sebagai evaluator ahli. Studi ini menunjukkan bahwa alternatif 1, yaitu pembangunan jembatan PCI Girder, merupakan alternatif yang terbaik. Kata-kata kunci: Analytical Hierarchy Process; analisis multi-sektoral; kriteria operasional; kinerja lalu lintas